Nifedipine does not prevent acute mountain sickness - Hohenhaus, Elke; Niroomand, Feraydoon; Goerre, S.; Vock, P.; Oelz, Oswald; Bärtsch, Peter (American journal of respiratory and critical care medicine, 1994)
Nifedipine has been shown effective for prevention and treatment of high altitude pulmonary edema (HAPE). Because acute mountain sickness (AMS) and HAPE may share common pathophysiologic mechanisms, we evaluate the prophylactic effect of nifedipine on the development of AMS in 27 mountaineers not susceptible to HAPE. They were randomly assigned to receive in a double-blind manner either nifedipine or placebo during rapid ascent to 4559 m and a subsequent three-day sojourn at this altitude. Nine of 14 subjects on nifedipine and eight of 13 subjects on placebo felt ill at high altitude. Pulmonary artery pressures (PAP) estimated by Doppler echocardiography were significantly lower with nifedipine, but arterial PO2, oxygen saturation, and alveolar-arterial oxygen pressure gradient were not significantly different between groups at high altitude. This study demonstrates that lowering PAP has no beneficial effect on gas exchange and symptoms of AMS in subjects not susceptible to HAPE. Therefore, nifedipine cannot be recommended for prevention of AMS, and its use in high altitude medicine should be limited to prevention and treatment of HAPE.
Gesehen am 17.01.2024